Sediment dynamics and tidal inlet relocation in mixed-energy settings: the case of Ancão inlet (Algarve - Portugal) - Concejo, Ana Vila (2012)
Tese de dout., Ciências do Mar, Faculdade de Ciências do Mar e do Ambiente, Univ. do Algarve, 2003